2021
DOI: 10.18502/ijpa.v16i2.6319
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Molecular Characterization of Toxocara cati Infection in Feral Cats in Alexandria City, Northern Egypt

Abstract: Background: This study was performed to determine the prevalence and to identify precisely Toxocara spp., which infects feral cats in Alexandria, Egypt based on morphological and molecular approaches. Methods: This cross-sectional study was carried out on 100 feral cats trapped from different areas of Alexandria during 2018. Adult male and female worms were recovered from small intestinal contents after euthanasia and dissection of cats. Distinct morphological features were initially determined using ava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
(61 reference statements)
0
0
0
Order By: Relevance
“…Variations among various research results may arise from differences in the results when addressing the terms prevalence, size or number of samples, sampling methodologies, nature of samples as coprological or necropsy, other epidemiological variables, statistical analysis, the use of different PCR techniques, and different DNA extraction techniques. Furthermore, DNA extraction procedures to extract T. cati genomic DNA include crushing, grinding, boiling, freeze-thawing, and application of kits [ 30 ]. The findings disagreed with those of another study, which indicated 30% were from the Himalayan breed and 32% were from the Shirazi breed.…”
Section: Discussionmentioning
confidence: 99%
“…Variations among various research results may arise from differences in the results when addressing the terms prevalence, size or number of samples, sampling methodologies, nature of samples as coprological or necropsy, other epidemiological variables, statistical analysis, the use of different PCR techniques, and different DNA extraction techniques. Furthermore, DNA extraction procedures to extract T. cati genomic DNA include crushing, grinding, boiling, freeze-thawing, and application of kits [ 30 ]. The findings disagreed with those of another study, which indicated 30% were from the Himalayan breed and 32% were from the Shirazi breed.…”
Section: Discussionmentioning
confidence: 99%